2009
DOI: 10.1590/s1807-59322009001000012
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Brazilian Medical Research. An Overview

Abstract: This article reviews 69 original research articles published in 6 Brazilian Medical Journals recently incorporated into the Institute for Scientific Information Journal of Citation Reports, with a view of making them comprehensively available to the readership of CLINICS within a subject category division. We expect this review to increase the visibility of a wide specter of original Brazilian research which may otherwise remain relatively unseen by the interested readershi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The main focus of the method is on trunk musculature; therefore, it can be classified as a program of "core stabilization" (Amorim, Sousa, & Santos, 2011;Akuthota & Nadler, 2004;Barr, Griggs, & Cadby, 2007;Stolze, Allison, & Childs, 2012). Pilates method has been considered as an important tool for rehabilitation and injury prevention (Anderson & Spector, 2000, Lim, Poh, Low, & Wong, 2012 and also has been the subject of recent trends in Brazilian scientific investigations (Bertolla, Baroni, Leal Junior, & Oltramari, 2007;Queiroz et al, 2010;Rocha-e-Silva, 2009;Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of the method is on trunk musculature; therefore, it can be classified as a program of "core stabilization" (Amorim, Sousa, & Santos, 2011;Akuthota & Nadler, 2004;Barr, Griggs, & Cadby, 2007;Stolze, Allison, & Childs, 2012). Pilates method has been considered as an important tool for rehabilitation and injury prevention (Anderson & Spector, 2000, Lim, Poh, Low, & Wong, 2012 and also has been the subject of recent trends in Brazilian scientific investigations (Bertolla, Baroni, Leal Junior, & Oltramari, 2007;Queiroz et al, 2010;Rocha-e-Silva, 2009;Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Brunoni and Fregni 1 found that more multicenter trials are being conducted. Glickman et al, 8 who discuss the economic benefits of globalization, found that clinical trials increasingly occur on a global scale and claim that one-third of trials are now being conducted in developing countries, 9 as pharmaceutical and medical device companies have embraced globalization. 8 This clearly raises numerous ethical concerns, including the testing of drugs for wealthy populations in human subjects of developing countries, the exacerbation of economic disparities and exploitation of low-income workers in developing countries, and their exposure to potentially dangerous drugs that could not be approved for testing in developed countries.…”
mentioning
confidence: 99%